The Relationship Between Parents' Economic Status And Students' Learning Motivation - Supit, Deisye (8ISC Abstract Proceedings; 8ISC Abstract Proceedings, 2022)
Learning motivation can be influenced by various factors, and one of the factors that influence is the economic status of parents. The research was carried out at SMP Negeri X in North Minahasa Regency with 111 respondents of grade VII D, E, F, G, and H students and parents of students where their children were registered in the 2016/2017 academic year. This study aims to find out the level of parents' economic status and the level of students' learning motivation and to see if there is a significant relationship between parents' economic status and students' learning motivation. This study has two variables, namely the economic status of parents as the dependent variable and students' learning motivation as the independent variable. The questionnaire used was adapted from (Santang, 2016). The mean score is used to find out the level of parents' economic status and the level of students' learning motivation and to describe the relationship between parents' economic status and students' learning motivation, and the Pearson product moment correlation is used. The results of this study are the level of parents' economic status is at a low level (mean = 2.38), for the level of student learning motivation is at a high level (mean = 3.12), and there is no significant relationship between parents' economic status and students' learning motivation ( p-value =.258 = .005). The conclusion of this study is that the parents of grade seven’s students of SMP Negeri X in the North Minahasa Regency mostly have incomes below the minimum wage set by the government, but this does not affect students' learning motivation because students still have a strong motivation to learn. Keywords : Economic status, parents, students, learning motivation